Thermally crosslinkable binder aqueous solution for lithium ion batteries, thermally crosslinkable slurry for lithium ion battery negative electrodes, lithium ion battery negative electrodes, and lithium ion batteries

JP7639279B2Active Publication Date: 2025-03-05ARAKAWA CHEM IND LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020139719
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-22
Filing Date
2020-08-21
Publication Date
2025-03-05
Estimated Expiration
2040-08-21

AI Technical Summary

Benefits of technology

【0015】 本開示に係るリチウムイオン電池用熱架橋性バインダー水溶液は、良好な放電容量維持率及び耐スプリングバック性をリチウムイオン電池に付与し、良好な密着性を電極に付与し、良好な貯蔵安定性をリチウムイオン電池負極用熱架橋性スラリーに付与しうる。また、本開示に係るリチウムイオン電池負極用熱架橋性スラリーは、優れた貯蔵安定性を有する。さらに、本開示に係る電極は優れた電極密着性を有する。そして、本開示に係る電池は、優れた放電容量維持率及び耐スプリングバック性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639279000001
    Figure 0007639279000001
  • Figure 0007639279000002
    Figure 0007639279000002
  • Figure 0007639279000003
    Figure 0007639279000003
Patent Text Reader

Abstract

To provide a thermal crosslinking binder aqueous solution for a lithium ion battery, a thermal crosslinking slurry for a lithium ion battery negative electrode, a negative electrode for a lithium ion battery, and a lithium ion battery.SOLUTION: A thermal crosslinking binder aqueous solution for a lithium ion battery is provided according to a disclosure hereof. The thermal crosslinking binder aqueous solution for a lithium ion battery comprises: a water-soluble poly(meth)acryl amide(A) including 2-60 mol% of a constituting unit originating from a (meth)acryl amide group-containing compound (a), and 10-50 mol% of a constituting unit originating from one or more unsaturated acids selected from a group consisting of an unsaturated carboxylic acid and an unsaturated sulfonic acid, or an inorganic salt (b) thereof; and 0.5-30 mol% of metal ions having a valence of 2 or greater to 100 mol% of acid groups that the component (b) has.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a thermally crosslinkable binder aqueous solution for a lithium ion battery, a thermally crosslinkable slurry for a lithium ion battery negative electrode, a lithium ion battery negative electrode, and a lithium ion battery. [Background technology]

[0002] Lithium-ion batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Therefore, in recent years, improvements to battery components such as electrodes have been studied in order to further improve the performance of lithium-ion batteries.

[0003] Both the positive and negative electrodes of a lithium-ion battery are manufactured by dispersing an electrode active material and a binder resin in a solvent to form a slurry, which is applied to both sides of a current collector (e.g., a metal foil), drying and removing the solvent to form an electrode layer, and then compression molding this using a roll press or the like.

[0004] Slurry for lithium-ion batteries mainly contains active material, binder, and solvent. For the binder, polyvinylidene fluoride (PVdF) has generally been used as a binder resin dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP), and styrene-butadiene emulsion (SBR latex) has been used as a binder resin for particulate resins dispersed in water.

[0005] In recent years, various electrode active materials have been proposed for lithium ion battery electrodes in order to increase the battery capacity. However, some electrode active materials tend to expand and contract with charging and discharging. Therefore, lithium ion battery electrodes that tend to expand and contract with charging and discharging undergo volume changes from the beginning of repeated charging and discharging (springback property), and tend to deteriorate the electrical properties such as cycle characteristics of lithium ion batteries using them.

[0006] In this field, therefore, studies have been made to solve the above problems by using binder resins, and it has been proposed, for example, that good charge-discharge characteristics can be obtained by using polyacrylamide as a binder for water-soluble resins (Patent Documents 1 and 2). It has also been proposed to suppress the expansion and contraction that accompanies the charge and discharge of active materials by adding a crosslinking agent to the particulate resin, which is the binder resin (Patent Document 3). The crosslinking agent usually causes a crosslinking reaction during the drying process after the slurry composition is applied to the current collector, forming crosslinks between particles of the particulate resin, etc. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-118908 A [Patent Document 2] JP 2015-106488 A [Patent Document 3] International Publication No. 2015 / 098507 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the polyacrylamides of Patent Documents 1 and 2 cannot be made to have a high molecular weight to the extent that the binder resin is insoluble in water, from the viewpoint of ensuring solubility in water, and as a result, there is a problem that the resistance to springback caused by the expansion of the active material is insufficient.

[0009] In some cases, the combined use of the crosslinking agent described in Patent Document 3 may not be effective even if a large amount is added. In such cases, if a large amount of crosslinking agent is added to exert the effect of the crosslinking agent, for example, resistance to springback, the adhesion of the electrode active material layer to the current collector may be reduced, and desired effects such as high-temperature cycle characteristics may not be obtained, so there is room for further improvement.

[0010] Furthermore, a binder composition containing a crosslinking agent and a particulate binder may deteriorate during storage from preparation to use, and may not exhibit the desired performance.

[0011] Therefore, an object of the present invention is to provide an aqueous thermally crosslinkable binder solution for lithium ion batteries, which imparts good discharge capacity retention rate and springback resistance to lithium ion batteries, good adhesion to electrodes, and good storage stability to a thermally crosslinkable slurry for lithium ion battery negative electrodes. [Means for solving the problem]

[0012] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, found that the above problems can be solved by using an aqueous binder solution containing poly(meth)acrylamide having a predetermined unsaturated monomer as a constituent component and a predetermined amount of a predetermined metal ion, thereby completing the present invention.

[0013] The present disclosure provides the following: (Item 1) 2 to 60 mol % of structural units derived from a (meth)acrylamide group-containing compound (a), and A water-soluble poly(meth)acrylamide (A) containing 10 to 50 mol % of structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b). and an aqueous thermally crosslinkable binder solution for lithium ion batteries, containing 0.5 to 30 mol % of divalent or higher metal ions relative to 100 mol % of the acid groups in the component (b). (Item 2) The aqueous thermally crosslinkable binder solution for lithium ion batteries according to the above items, wherein the water-soluble poly(meth)acrylamide (A) contains 15 to 75 mol % of structural units derived from the hydroxyl group-containing (meth)acrylic ester (c). (Item 3) Item 10. The aqueous thermally crosslinkable binder solution for lithium ion batteries according to any one of the preceding items, wherein the divalent or higher metal ion is a calcium ion. (Item 4) A thermally crosslinkable slurry for a lithium ion battery negative electrode, comprising the thermally crosslinkable binder aqueous solution for a lithium ion battery according to any one of the above items and a negative electrode active material. (Item 5) A negative electrode for a lithium ion battery, obtained by applying the thermally crosslinkable slurry for a lithium ion battery negative electrode described in the above item to a current collector, followed by drying and curing. (Item 6) A lithium ion battery comprising the lithium ion battery negative electrode described in the above item.

[0014] In the present disclosure, one or more of the above-described features may be provided in further combinations in addition to the combinations explicitly stated. Effect of the Invention

[0015] The thermally crosslinkable binder aqueous solution for lithium ion batteries according to the present disclosure can impart good discharge capacity retention and springback resistance to lithium ion batteries, good adhesion to electrodes, and good storage stability to thermally crosslinkable slurry for lithium ion battery negative electrodes. The thermally crosslinkable slurry for lithium ion battery negative electrodes according to the present disclosure has excellent storage stability. Furthermore, the electrodes according to the present disclosure have excellent electrode adhesion. And the batteries according to the present disclosure have excellent discharge capacity retention and springback resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Throughout this disclosure, the range of the values ​​of the physical properties, contents, etc. may be set as appropriate (for example, by selecting from the upper and lower limit values ​​described in each item below). Specifically, when A4, A3, A2, A1 (where A4>A3>A2>A1) are exemplified as the upper and lower limits of the value α, the range of the value α is exemplified as A4 or less, A3 or less, A2 or less, A1 or more, A2 or more, A3 or more, A1 to A2, A1 to A3, A1 to A4, A2 to A3, A2 to A4, A3 to A4, etc.

[0017] [Thermal crosslinking binder aqueous solution for lithium ion batteries: also called aqueous solution] The present disclosure relates to a polymerizable composition comprising 2 to 60 mol % of a structural unit derived from a (meth)acrylamide group-containing compound (a), and A water-soluble poly(meth)acrylamide (A) (also referred to as component (A)) containing 10 to 50 mol % of structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b). The present invention also provides an aqueous thermally crosslinkable binder solution for lithium ion batteries, which contains 0.5 to 30 mol % of divalent or higher metal ions relative to 100 mol % of the acid groups in the component (b).

[0018] In this disclosure, "water-soluble" means that when 0.5 g of the compound is dissolved in 100 g of water at 25°C, the insoluble matter is less than 0.5% by mass (less than 2.5 mg).

[0019] In the present disclosure, "(meth)acrylic" means "at least one selected from the group consisting of acrylic and methacrylic". Similarly, "(meth)acrylate" means "at least one selected from the group consisting of acrylate and methacrylate". In addition, "(meth)acryloyl" means "at least one selected from the group consisting of acryloyl and methacryloyl".

[0020] <(Meth)acrylamide group-containing compound (a): also referred to as component (a)> In the present disclosure, the term "(meth)acrylamide group-containing compound" refers to a compound having a (meth)acrylamide group. The (meth)acrylamide group-containing compound may be used alone or in combination of two or more kinds.

[0021] In one embodiment, the (meth)acrylamide group-containing compound has the following structural formula: [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 and R 3are each independently a hydrogen atom, a substituted or unsubstituted alkyl group, or an acetyl group; 2 and R 3 are groups that together form a ring structure, and R 4 and R 5 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, a hydroxyl group, an amino group (-NR a R b (R a and R b are each independently a hydrogen atom or a substituted or unsubstituted alkyl group, and an acetyl group. Examples of the substituent of the substituted alkyl group include a hydroxy group, an amino group, and an acetyl group. 2 and R 3 Examples of the group that combines with each other to form a ring structure include a morpholyl group. It is expressed by:

[0022] Examples of the alkyl group include a straight-chain alkyl group, a branched alkyl group, and a cycloalkyl group.

[0023] A straight chain alkyl group is -C n H 2n+1 (n is an integer of 1 or more). Examples of the straight-chain alkyl group include a methyl group, an ethyl group, a propyl group, a n-butyl group, a n-pentyl group, a n-hexyl group, a n-heptyl group, a n-octyl group, a n-nonyl group, and a n-decamethyl group.

[0024] A branched alkyl group is a group in which at least one hydrogen atom of a linear alkyl group is replaced by an alkyl group. Examples of branched alkyl groups include an i-propyl group, an i-butyl group, an s-butyl group, a t-butyl group, a diethylpentyl group, a trimethylbutyl group, a trimethylpentyl group, and a trimethylhexyl group.

[0025] Examples of the cycloalkyl group include a monocyclic cycloalkyl group, a bridged ring cycloalkyl group, and a condensed ring cycloalkyl group.

[0026] In the present disclosure, a monocyclic ring refers to a ring structure formed by a carbon covalent bond and having no internal bridge structure. A fused ring refers to a ring structure in which two or more monocyclic rings share two atoms (i.e., each ring shares only one side (fused) with each other). A bridged ring refers to a ring structure in which two or more monocyclic rings share three or more atoms.

[0027] Examples of the monocyclic cycloalkyl group include a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclodecyl group, and a 3,5,5-trimethylcyclohexyl group.

[0028] Examples of the bridged ring cycloalkyl group include a tricyclodecyl group, an adamantyl group, and a norbornyl group.

[0029] The condensed ring cycloalkyl group is exemplified by a bicyclodecyl group.

[0030] Examples of the (meth)acrylamide group-containing compound (a) include (meth)acrylamide, N-isopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-methylol(meth)acrylamide, diacetone(meth)acrylamide, maleic acid amide, (meth)acryloylmorpholine, hydroxyethyl(meth)acrylamide, and salts thereof, and examples of the salts include dimethylaminopropyl(meth)acrylamide methyl chloride quaternary salt, dimethylaminoethyl(meth)acrylate benzyl chloride quaternary salt, etc. Among these, when (meth)acrylamide, particularly acrylamide, is used, it is possible to produce a binder that not only reduces water absorption while maintaining water solubility, but also reduces irreversible capacity, has high interaction with electrode active materials, and has high dispersibility of the slurry and high binding between electrode active materials inside the electrode.

[0031] The upper and lower limits of the content of structural units derived from a (meth)acrylamide group-containing compound relative to 100 mol % of all structural units of the component (A) are, for example, 60, 59, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9, 5, 3, 2 mol %, etc. In one embodiment, the above content is preferably in the range of 2 to 60 mol %.

[0032] The upper and lower limits of the content of structural units derived from a (meth)acrylamide group-containing compound relative to 100% by mass of all structural units of the component (A) are, for example, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9, 5, 4, 2, 1% by mass, etc. In one embodiment, the content is preferably 1 to 70% by mass.

[0033] <One or more unsaturated acids or inorganic salts thereof selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids (b): also referred to as component (b)> As the (b) component, various known substances can be used without particular limitation, and may be used alone or in combination of two or more. In this disclosure, when compound A corresponds to both component (a) and component (b), the compound A is considered to be component (b). In this disclosure, an inorganic salt of one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids refers to a salt in which the cation portion is a metal cation.

[0034] Examples of the unsaturated carboxylic acid include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid.

[0035] Examples of unsaturated sulfonic acids include α,β-ethylenically unsaturated sulfonic acids such as vinyl sulfonic acid, styrene sulfonic acid, and (meth)allyl sulfonic acid; (meth)acrylamide t-butyl sulfonic acid, 2-(meth)acrylamide-2-methylpropane sulfonic acid, 2-(meth)acrylamide-2-hydroxypropane sulfonic acid, 3-sulfopropane (meth)acrylic acid ester, and bis-(3-sulfopropyl)itaconic acid ester.

[0036] Examples of inorganic salts include typical metal salts and transition metal salts.

[0037] Examples of typical metal salts include alkali metal salts, alkaline earth metal salts, and Group 13 metal salts.

[0038] Examples of the alkali metal salt include lithium salts, sodium salts, and potassium salts.

[0039] Examples of the alkaline earth metal salt include magnesium salts and calcium salts.

[0040] Examples of Group 13 metal salts include aluminum salts.

[0041] The transition metal salt is exemplified by iron salts.

[0042] The upper and lower limits of the content of divalent or higher metal ions relative to 100 mol % of acid groups in the component (b) are, for example, 30, 25, 20, 15, 10, 9, 5, 4, 2, 1, 0.9, 0.5 mol %, etc. In one embodiment, the content is preferably 0.5 to 30 mol %.

[0043] In one embodiment, the divalent or higher metal ion is preferably a divalent metal ion, more preferably an alkaline earth metal ion, and further preferably a calcium ion from the viewpoint of solubility in water.

[0044] The upper and lower limits of the content of monovalent metal ions relative to 100 mol % of acid groups in the component (b) are, for example, 99.5, 99, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 mol %, etc. In one embodiment, the content is preferably 10.0 to 99.5 mol %.

[0045] The upper and lower limits of the content of the structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b) relative to 100 mol % of all structural units of the component (A) are, for example, 50, 45, 40, 35, 30, 25, 20, 15, 10 mol %, etc. In one embodiment, the content is preferably 10 to 50 mol %.

[0046] The upper and lower limits of the content of the structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b) relative to 100% by mass of all structural units of the component (A) are, for example, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 5% by mass, etc. In one embodiment, the above content is preferably 5 to 70% by mass.

[0047] <Hydroxyl group-containing (meth)acrylic ester (c): Also referred to as component (c)> As the component (c), various known substances can be used without particular limitation, and they may be used alone or in combination of two or more. In one embodiment, the hydroxyl group-containing (meth)acrylic ester is preferably a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms.

[0048] In the present disclosure, a "hydroxyalkyl group having 2 to 4 carbon atoms" refers to a group in which one of the hydrogen atoms constituting an alkyl group having 2 to 4 carbon atoms has been substituted with a hydroxy group.

[0049] Hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 2 to 4 carbon atoms include 1-hydroxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, 1-hydroxy-2-methylethyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate. Examples include butyl, 4-hydroxybutyl (meth)acrylate, 1-hydroxy-1-methyl-propyl (meth)acrylate, 2-hydroxy-1-methyl-propyl (meth)acrylate, 3-hydroxy-1-methyl-propyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 1-hydroxy-2-methyl-propyl (meth)acrylate, 2-hydroxy-2-methyl-propyl (meth)acrylate, 3-hydroxy-2-methyl-propyl (meth)acrylate, and 1,1-dimethyl-2-hydroxyethyl (meth)acrylate.

[0050] The upper and lower limits of the content of the structural units derived from the hydroxyl group-containing (meth)acrylic ester (c) relative to 100 mol % of all structural units of the component (A) are, for example, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 17, 15 mol %, etc. In one embodiment, the content is preferably 15 to 75 mol %.

[0051] The upper and lower limits of the content of the structural units derived from the hydroxyl group-containing (meth)acrylic ester (c) relative to 100% by mass of all structural units of the component (A) are, for example, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20% by mass, etc. In one embodiment, the content is preferably 20 to 80% by mass.

[0052] The upper and lower limits of the substance amount ratio of component (a) to component (b) contained in all structural units of component (A) [substance amount of component (a) / substance amount of component (b)] are exemplified as 6, 5.5, 5, 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0.04, etc. In one embodiment, the substance amount ratio is preferably 0.04 to 6.

[0053] The upper and lower limits of the substance amount ratio of the component (a) to the component (c) contained in all structural units of the component (A) [substance amount of the component (a) / substance amount of the component (c)] are exemplified as 4, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0.04, 0.02, etc. In one embodiment, the substance amount ratio is preferably 0.02 to 4.

[0054] The upper and lower limits of the substance amount ratio of the component (b) to the component (c) contained in all structural units of the component (A) [substance amount of the component (b) / substance amount of the component (c)] are exemplified as 3.3, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.25, 0.2, 0.15, 0.13, etc. In one embodiment, the substance amount ratio is preferably 0.13 to 3.3.

[0055] The upper and lower limits of the mass ratio of the component (a) to the component (b) contained in all structural units of the component (A) [mass of the component (a) / mass of the component (b)] are, for example, 14, 12, 10, 9, 8, 7, 6, 5, 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.25, 0.1, 0.09, 0.05, 0.01, etc. In one embodiment, the above mass ratio is preferably 0.01 to 14.

[0056] The upper and lower limits of the mass ratio of the component (a) to the component (c) contained in all structural units of the component (A) [mass of the component (a) / mass of the component (c)] are, for example, 3.5, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.25, 0.1, 0.09, 0.05, 0.01, etc. In one embodiment, the above mass ratio is preferably 0.01 to 3.5.

[0057] The upper and lower limits of the mass ratio of the component (b) to the component (c) contained in all structural units of the component (A) [mass of the component (b) / mass of the component (c)] are, for example, 3.5, 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.25, 0.2, 0.15, 0.12, 0.1, 0.09, 0.06, etc. In one embodiment, the above mass ratio is preferably 0.06 to 3.5.

[0058] <Monomers other than components (a), (b), and (c): Also called component (d)> All of the constituent units of component (A) may be derived from a monomer (component (d)) that does not fall under any of components (a), (b), or (c), as long as the desired effects of the present invention are not impaired. Component (d) may be used alone or in combination of two or more. Examples of component (d) include unsaturated phosphoric acid or a salt thereof, unsaturated carboxylate ester not containing a hydroxyl group, α,β-unsaturated nitrile, conjugated diene, and aromatic vinyl compound.

[0059] Examples of unsaturated phosphoric acids include vinylphosphonic acid, vinyl phosphate, bis((meth)acryloxyethyl)phosphate, diphenyl-2-(meth)acryloyloxyethyl phosphate, dibutyl-2-(meth)acryloyloxyethyl phosphate, dioctyl-2-(meth)acryloyloxyethyl phosphate, monomethyl-2-(meth)acryloyloxyethyl phosphate, and 3-(meth)acryloxy-2-hydroxypropane phosphoric acid.

[0060] The content of the structural units derived from unsaturated phosphoric acid or a salt thereof is not particularly limited, but taking into consideration the reaction with the above-mentioned component (b), it is preferably less than 40 mol% (for example, 30, 20, 19, 15, 10, 5, less than 1 mol%, or 0 mol%) relative to 100 mol% of all structural units of the component (A).

[0061] The content of structural units derived from unsaturated phosphoric acid or a salt thereof relative to 100% by mass of all structural units of the component (A) is preferably less than 40% by mass (for example, 30, 20, 19, 15, 10, 5, less than 1% by mass, or 0% by mass).

[0062] The hydroxyl-free unsaturated carboxylic acid ester is preferably a hydroxyl-free (meth)acrylic acid ester. Examples of the hydroxyl-free (meth)acrylic acid ester include a hydroxyl-free linear (meth)acrylic acid ester, a hydroxyl-free branched (meth)acrylic acid ester, a hydroxyl-free alicyclic (meth)acrylic acid ester, and a hydroxyl-free substituted (meth)acrylic acid ester.

[0063] Examples of non-hydroxyl group-containing linear (meth)acrylate esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-amyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate.

[0064] Examples of non-hydroxyl group-containing branched (meth)acrylic acid esters include i-propyl (meth)acrylate, i-butyl (meth)acrylate, i-amyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0065] Examples of the non-hydroxyl group-containing alicyclic (meth)acrylic acid ester include cyclohexyl (meth)acrylate.

[0066] The content of the structural units derived from the non-hydroxyl group-containing unsaturated carboxylic acid ester is not particularly limited, but the use of the non-hydroxyl group-containing unsaturated carboxylic acid ester can suppress curling of the electrode due to a decrease in the glass transition temperature of the component (A). On the other hand, in consideration of the springback resistance of the lithium ion battery, the content of the structural units derived from the non-hydroxyl group-containing unsaturated carboxylic acid ester is preferably less than 40 mol% (e.g., 30, 20, 19, 15, 10, 5, less than 1 mol%, or 0 mol%) relative to 100 mol% of all structural units of the component (A).

[0067] In one embodiment, the content of structural units derived from non-hydroxyl group-containing unsaturated carboxylic acid ester relative to 100% by mass of all structural units of the component (A) is preferably less than 40% by mass (for example, 30, 20, 19, 15, 10, 5, less than 1% by mass, or 0% by mass).

[0068] Examples of the α,β-unsaturated nitrile include (meth)acrylonitrile, α-chloro(meth)acrylonitrile, α-ethyl(meth)acrylonitrile, vinylidene cyanide, etc. Among these, (meth)acrylonitrile is preferred, and acrylonitrile is particularly preferred.

[0069] The α,β-unsaturated nitrile can be suitably used for the purpose of imparting flexibility to the electrode. The content of the structural unit derived from the α,β-unsaturated nitrile is not particularly limited, but is preferably less than 40 mol% (for example, 30, 20, 19, 15, 10, 5, less than 1 mol%, 0 mol%) relative to 100 mol% of the total structural units of the component (A). By being less than 40 mol% relative to 100 mol% of the total structural units of the component (A), the electrode layer of the above slurry becomes uniform while maintaining the solubility of the component (A) in water, and it becomes easier to exhibit flexibility.

[0070] In one embodiment, the content of structural units derived from an α,β-unsaturated nitrile relative to 100% by mass of all structural units of the component (A) is preferably less than 40% by mass (for example, 30, 20, 19, 15, 10, 5, less than 1% by mass, or 0% by mass).

[0071] Examples of conjugated dienes include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, and substituted and side-chain conjugated hexadienes.

[0072] The content of the structural units derived from the conjugated diene is not particularly limited, but from the viewpoint of the springback resistance of the lithium ion battery, it is preferably less than 10 mol %, and more preferably 0 mol %, of 100 mol % of all structural units of the component (A).

[0073] In one embodiment, the content of structural units derived from conjugated dienes relative to 100% by mass of all structural units of the component (A) is preferably less than 10% by mass, and more preferably 0% by mass.

[0074] Examples of aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, and divinylbenzene.

[0075] The content of the structural unit derived from the aromatic vinyl compound is not particularly limited, but from the viewpoint of the springback resistance of the lithium ion battery, it is preferably less than 10 mol % of the total structural units of the component (A) (100 mol %), and more preferably 0 mol %. In one embodiment, the component (A) does not have an aromatic ring group.

[0076] In one embodiment, the content of structural units derived from an aromatic vinyl compound relative to 100% by mass of all structural units of the component (A) is preferably less than 10% by mass, and more preferably 0% by mass.

[0077] The proportion of structural units derived from component (d) other than the unsaturated phosphoric acid or salt thereof, hydroxyl group-free unsaturated carboxylate ester, α,β-unsaturated nitrile, conjugated diene, and aromatic vinyl compound in all structural units of component (A) is less than 10 mol%, less than 5 mol%, less than 1 mol%, less than 0.1 mol%, less than 0.01 mol%, or 0 mol%, relative to 100 mol% of all structural units of component (A); and less than 10 mass%, less than 5 mass%, less than 1 mass%, less than 0.5 mass%, less than 0.1 mass%, less than 0.01 mass%, or 0 mass%, relative to 100 mass% of all structural units of component (A).

[0078] The method for introducing divalent or higher metal ions into the water-soluble poly(meth)acrylamide (A) is as follows: (1) A method of introducing the amine group by polymerizing all of the structural units of the component (A) including the (meth)acrylamide group-containing compound (a), an unsaturated carboxylic acid, and an unsaturated sulfonic acid to produce a water-soluble poly(meth)acrylamide (A), and then neutralizing the resulting product with a salt of a divalent or higher metal ion; (2) A method for producing a water-soluble poly(meth)acrylamide (A) by polymerizing all of the structural units of the component (A) containing a (meth)acrylamide group-containing compound (a) and a salt of a divalent or higher metal ion of an unsaturated carboxylic acid and an unsaturated sulfonic acid. Either of the above may be used.

[0079] Examples of the salt of the divalent or higher metal ion include salts of divalent or higher typical metals and salts of divalent or higher transition metals.

[0080] Examples of typical metal salts having a valence of two or more include alkaline earth metal salts and Group 13 metal salts.

[0081] Examples of the alkaline earth metal salt include magnesium salts and calcium salts.

[0082] Examples of magnesium salts include magnesium hydroxide, magnesium chloride, magnesium fluoride, magnesium bromide, magnesium acetate, magnesium sulfate, magnesium carbonate, magnesium phosphate, magnesium hydrogen carbonate, and the like.

[0083] Examples of calcium salts include calcium hydroxide, calcium chloride, calcium fluoride, calcium bromide, calcium acetate, calcium sulfate, calcium carbonate, calcium phosphate, calcium hydrogen carbonate, and the like.

[0084] Examples of Group 13 metal salts include aluminum salts.

[0085] Examples of aluminum salts include aluminum hydroxide, aluminum chloride, aluminum fluoride, aluminum bromide, aluminum acetate, aluminum sulfate, aluminum phosphate, and aluminum carbonate.

[0086] The transition metal salt is exemplified by iron salts.

[0087] Examples of iron salts include iron hydroxide, iron chloride, iron fluoride, iron bromide, iron acetate, iron sulfate, iron phosphate, and iron carbonate.

[0088] In one embodiment, the divalent or higher metal salt is preferably a divalent metal salt, more preferably an alkaline earth metal salt, and further preferably a calcium salt from the viewpoint of solubility in water.

[0089] The carboxylic acid group or sulfonic acid group of the water-soluble poly(meth)acrylamide (A) and the metal ion are in an ionized state in the slurry. On the other hand, after the slurry is applied to the metal foil, in the process of drying the water, as the water decreases, the acid group and the metal ion interact (ion complex), and after the water dries, the acid group forms a metal salt. In the drying process, the water does not volatilize from the contact surface with the copper foil, but volatilizes unilaterally from the air surface. In general, when a water-soluble polymer is used as a binder, the polymer migrates (migrates) to the air surface side due to the drying of the water, and the copper foil side becomes diluted, resulting in a phenomenon in which the adhesion of the copper foil surface deteriorates. As in the present disclosure, when the acid group is neutralized with a divalent or higher metal ion, an ion complex is formed when the concentration is increased during the drying process, and the polymers form a network by bridging the metal ions, so the migration described above is unlikely to occur. It should be noted that the above is merely one theory, and it is not intended that the present invention be restricted to the above theory.

[0090] <Method of manufacturing component (A)> The component (A) can be synthesized by various known polymerization methods, preferably radical polymerization methods. Specifically, it is preferable to add a radical polymerization initiator and, if necessary, a chain transfer agent to a monomer mixture containing the above components, and carry out a polymerization reaction at a reaction temperature of 50 to 100° C. while stirring. The reaction time is not particularly limited, and is preferably 1 to 10 hours.

[0091] As the radical polymerization initiator, various known ones can be used without any particular limitation. Examples of the radical polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate; redox-based polymerization initiators combining the above-mentioned persulfates with a reducing agent such as sodium hydrogen sulfite; and azo-based initiators such as 2,2'-azobis-2-amidinopropane dihydrochloride. The amount of the radical polymerization initiator used is not particularly limited, but is preferably 0.05 to 5.0% by mass, more preferably 0.1 to 3.0% by mass, based on 100% by mass of the monomer group that gives the component (A).

[0092] For the purpose of improving production stability, before the radical polymerization reaction and / or when the obtained component (A) is dissolved in water, the pH of the reaction solution may be adjusted with a common neutralizing agent such as ammonia, organic amine, potassium hydroxide, sodium hydroxide, lithium hydroxide, etc. In this case, the pH is preferably 2 to 11. For the same purpose, it is also possible to use a metal ion-sequestering agent such as ethylenediaminetetraacetic acid (EDTA) or a salt thereof.

[0093] <Physical properties of component (A)> Examples of upper and lower limits of the glass transition temperature of the component (A) are 160, 155, 150, 145, 140, 135, 130, 125, 120, 115, 110, 105, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, and 0° C. In one embodiment, 0° C. or higher is preferable, and from the viewpoint of mechanical strength and heat resistance, 30° C. or higher is more preferable.

[0094] The glass transition temperature of component (A) can be adjusted by the combination of monomers. The glass transition temperature of component (A) can be calculated from the glass transition temperature (Tg) (absolute temperature: K) of the homopolymer of the monomers and their mass fractions based on the Fox formula shown below. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)+···+(W n / Tg n ) [Wherein, Tg is the glass transition temperature (K) of the polymer to be determined, W1 to W n is the mass fraction of each monomer, Tg1 to Tg n indicates the glass transition temperature (K) of the homopolymer of each monomer.

[0095] For example, the glass transition temperature is 165°C for homopolymer of acrylamide, 106°C for homopolymer of acrylic acid, -15°C for homopolymer of hydroxyethyl acrylate, and 105°C for homopolymer of acrylonitrile. The monomer composition constituting component (A) can be determined so as to obtain a component having a desired glass transition temperature. The glass transition temperature of the homopolymer of the monomer can be measured, for example, under conditions of heating from -100°C to 300°C (heating rate 10°C / min.) using a DSC (differential scanning calorimeter), DTA (differential thermal analyzer), TMA (thermomechanical analyzer), or the like. Values ​​described in literature can also be used. Examples of literature include "Chemical Handbook Basics II Edited by the Chemical Society of Japan (Revised 5th Edition)", p. 325, and the like.

[0096] The gel fraction of the cured product of component (A) is not particularly limited, but examples of upper and lower limits of the gel fraction of the cured product of component (A) are 99.9%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, etc. In one embodiment, from the viewpoint of the effect of expressing springback resistance due to charge / discharge cycles, it is preferably 20% or more, and more preferably 25% or more.

[0097] The gel fraction of the cured product of component (A) is calculated using the following formula: Gel fraction (%) = {water insoluble residue (g) / mass of solid resin (g)} x 100 This is the value calculated by:

[0098] In one embodiment, the curing conditions for the cured product are, for example, 120° C. for 4 hours.

[0099] The gel fraction is measured, for example, as follows. An appropriate amount (for example, 10 g) of a thermally crosslinkable binder aqueous solution for lithium ion batteries containing water-soluble poly(meth)acrylamide (A) is placed in an appropriate container (for example, an ointment can (manufactured by Sogo Rikagaku Glass Manufacturing Co., Ltd., product name "Ointment Can Tinplate")) and dried under appropriate drying conditions (for example, in a circulating air dryer (manufactured by Advantec Toyo Co., Ltd., product name "Air-Blowing Constant Temperature Dryer DSR420DA") at 120°C for 4 hours), to obtain a solid resin after thermal crosslinking. The mass of the solid resin is accurately measured at 25°C using an appropriate mass meter (for example, manufactured by Sartorius Japan Co., Ltd., product name "Standard Balance CPA324S"). The measured solid resin is transferred to an appropriate container (e.g., a 300 mL beaker) containing an appropriate amount (e.g., 150 mL) of pure water, and immersed in the water under appropriate conditions (e.g., at 25°C for 3 hours) while stirring using an appropriate magnetic stirrer (e.g., Tokyo Rikakikai Co., Ltd., product name "Powerful Magnetic Stirrer RCX-1000D"), and then filtered under reduced pressure using an appropriate device (e.g., Kiriyama Funnel (manufactured by Kiriyama Seisakusho Co., Ltd., product name "Kiriyama Funnel SB-60") and a suction bell (manufactured by Kiriyama Seisakusho Co., Ltd., product name "Suction Bell VKB-200"), and filter paper (manufactured by Kiriyama Seisakusho Co., Ltd., "No. 50B")). Thereafter, the insoluble residue remaining on the filter paper is dried under appropriate conditions (e.g., 120°C for 3 hours) in an appropriate dryer (e.g., the above-mentioned air circulating dryer), and the mass of the insoluble residue is accurately measured at an appropriate temperature (e.g., 25°C) using an appropriate mass meter (e.g., the above-mentioned mass meter), and the gel fraction of the resin after thermal crosslinking of the water-soluble battery binder is calculated using the above formula.

[0100] The thermal crosslinking of the water-soluble poly(meth)acrylamide (A) is believed to be due to the amide group derived from the (meth)acrylamide group-containing compound (a) and the hydroxyl group derived from the hydroxyl group-containing (meth)acrylic ester (c). The molar ratio of the amide group to the hydroxyl group (amide group / hydroxyl group) in the water-soluble poly(meth)acrylamide (A) is not particularly limited, but it is preferable that the amide group is in excess. The upper and lower limits of the molar ratio of the amide group to the hydroxyl group (amide group / hydroxyl group) are 19, 18, 17.5, 15, 12.5, 10, 9, 7.5, 5, 2.5, 1.2, 1.0, etc. are exemplified. In one embodiment, the amide group / hydroxyl group=1.0 to 19.0 is preferable, and 1.2 to 18.0 is more preferable. By satisfying the above, it is believed that the effect of expressing springback resistance accompanying charge / discharge cycles can be obtained without impairing the adhesion of the active material layer to the current collector, but the present invention is not intended to be limited thereto.

[0101] The weight average molecular weight (Mw) of the (A) component is not particularly limited, but examples of the upper and lower limits include 7 million, 6.5 million, 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, etc. In one embodiment, from the viewpoint of the dispersion stability of the slurry, it is preferably 300,000 to 7 million, more preferably 350,000 to 6 million.

[0102] The number average molecular weight (Mn) of the component (A) is not particularly limited, but examples of the upper and lower limits include 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 300,000, 200,000, 100,000, 50,000, 10,000, etc. In one embodiment, the number average molecular weight (Mn) of the component (A) is preferably 10,000 or more.

[0103] The weight average molecular weight and number average molecular weight can be determined, for example, as a polyacrylic acid equivalent value measured in an appropriate solvent by gel permeation chromatography (GPC).

[0104] Examples of the upper and lower limits of the molecular weight distribution (Mw / Mn) of the component (A) are 15, 14, 13, 11, 10, 9, 7.5, 5, 4, 3, 2.9, 2.5, 2, 1.5, 1.1, etc. In one embodiment, the molecular weight distribution (Mw / Mn) of the component (A) is preferably 1.1 to 15.

[0105] The B-type viscosity of an aqueous solution containing 13% by mass of component (A) is not particularly limited, but examples of the upper and lower limits include 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, 40,000, 30,000, 20,000, 10,000 mPa s, etc. In one embodiment, the B-type viscosity is preferably in the range of 1,000 to 100,000 mPa s.

[0106] The Brookfield viscosity is measured using a Brookfield viscometer such as the "Brookfield Viscometer Model BM" manufactured by Toki Sangyo Co., Ltd.

[0107] Examples of the upper and lower limits of the pH of the aqueous solution of the thermally crosslinkable binder for lithium ion batteries include 7, 6.9, 6.5, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, and 5. In one embodiment, the pH of the aqueous solution of the thermally crosslinkable binder for lithium ion batteries is preferably 5 to 7 from the viewpoint of solution stability, and more preferably 5 or more and less than 7. From the viewpoint of preventing a decrease in slurry dispersibility and Coulombic efficiency, the pH is preferably 5 or more, and from the viewpoint of preventing a decrease in flexibility, the pH is preferably 7 or less.

[0108] The pH can be measured at 25° C. using a glass electrode pH meter (for example, product name "pH Meter D-52" manufactured by Horiba, Ltd.).

[0109] The upper and lower limits of the content of the water-soluble poly(meth)acrylamide (A) relative to 100% by mass of the aqueous thermally crosslinkable binder solution for lithium ion batteries are, for example, 20, 19, 15, 14, 12, 10, 9, 7, 6, 5% by mass, etc. In one embodiment, the content of the water-soluble poly(meth)acrylamide (A) relative to 100% by mass of the aqueous thermally crosslinkable binder solution for lithium ion batteries is preferably 5 to 20% by mass.

[0110] The upper and lower limits of the water content relative to 100% by mass of the thermally crosslinkable binder aqueous solution for lithium ion batteries are, for example, 95, 90, 85, 80% by mass, etc. In one embodiment, the water content relative to 100% by mass of the thermally crosslinkable binder aqueous solution for lithium ion batteries is preferably 80 to 95% by mass.

[0111] The upper and lower limits of the mass ratio of the component (A) to water contained in the aqueous thermally crosslinkable binder solution for lithium ion batteries [mass of component (A) / mass of water] are, for example, 0.25, 0.2, 0.15, 0.1, 0.05, etc. In one embodiment, the mass ratio of the component (A) to water contained in the aqueous thermally crosslinkable binder solution for lithium ion batteries is preferably 0.05 to 0.25.

[0112] <Dispersion (emulsion)> In one embodiment, the aqueous thermally crosslinkable binder solution for a lithium ion battery includes a dispersion (emulsion).

[0113] Dispersions (emulsions) include styrene-butadiene copolymer latex, polystyrene polymer latex, polybutadiene polymer latex, acrylonitrile-butadiene copolymer latex, polyurethane polymer latex, polymethyl methacrylate polymer latex, methyl methacrylate-butadiene copolymer latex, polyacrylate polymer latex, vinyl chloride polymer latex, vinyl acetate polymer emulsion, vinyl acetate-ethylene copolymer emulsion, polyethylene emulsion, carboxy-modified styrene butadiene copolymer latex, poly ... Examples include diene copolymer resin emulsion, acrylic resin emulsion, polyethylene, polypropylene, polyethylene terephthalate, polyamide (PA), polyimide (PI), polyamideimide (PAI), aromatic polyamide, alginic acid and its salts, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), and the like.

[0114] Examples of upper and lower limits of the content of the dispersion (emulsion) relative to 100 mass% of the component (A) are 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 19, 17, 15, 13, 10, 9, 7, 5, 4, 2, 1, 0 mass%, etc. In one embodiment, from the viewpoints of electrode flexibility and discharge capacity retention rate, the content is preferably 0 to 100 mass%.

[0115] <Thickener> In one embodiment, the aqueous thermally crosslinkable binder solution for a lithium ion battery contains a thickener.

[0116] Examples of thickeners include cellulose-based polymers such as carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohols such as copolymers of acrylic acid or acrylates and vinyl alcohol, and copolymers of maleic anhydride or maleic acid or fumaric acid and vinyl alcohol; polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, and hydrogenated acrylonitrile-butadiene copolymers.

[0117] Examples of upper and lower limits for the content of the thickener relative to 100% by mass of the component (A) are 50, 45, 40, 35, 30, 25, 20, 19, 17, 15, 13, 10, 9, 7, 5, 4, 2, 1, 0% by mass, etc. In one embodiment, the content is preferably 0 to 50% by mass.

[0118] <Additives> The aqueous solution of the thermally crosslinkable binder for lithium ion batteries may contain an additive that does not fall under any of the following: component (A), water, dispersion (emulsion), and thickener. Examples of the additive include a dispersant, a leveling agent, an antioxidant, a particulate polymer, a crosslinking agent, and a hydroxysilyl compound. Examples of the content of the additive include 0 to 5% by mass, less than 1% by mass, less than 0.1% by mass, and less than 0.01% by mass, relative to 100% by mass of the component (A), and examples of the content of the additive include 0 to 5% by mass, less than 1% by mass, less than 0.1% by mass, less than 0.01% by mass, and 0% by mass, relative to 100% by mass of the aqueous solution.

[0119] Examples of the dispersant include anionic dispersants, cationic dispersants, nonionic dispersants, and polymer dispersants.

[0120] Examples of the leveling agent include surfactants such as alkyl surfactants, silicon surfactants, fluorine surfactants, and metal surfactants. By using a surfactant, it is possible to prevent repellency during coating and improve the smoothness of the slurry layer (coating layer).

[0121] Examples of the antioxidant include phenol compounds, hydroquinone compounds, organic phosphorus compounds, sulfur compounds, phenylenediamine compounds, and polymeric phenol compounds. The polymeric phenol compounds are polymers having a phenol structure in the molecule. The weight average molecular weight of the polymeric phenol compounds is preferably 200 to 1000, and more preferably 600 to 700.

[0122] Examples of the crosslinking agent include formaldehyde, glyoxal, hexamethylenetetramine, urea formaldehyde resin, methylolmelamine resin, carbodiimide compounds, polyfunctional epoxy compounds, oxazoline compounds, polyfunctional hydrazide compounds, isocyanate compounds, melamine compounds, urea compounds, and mixtures thereof.

[0123] The hydroxysilyl compound means a compound having a structure in which a hydroxy group (-OH) is directly bonded to a silicon atom, the trihydroxysilyl compound means a compound having a trihydroxysilyl group (-Si(OH)3), and the tetrahydroxysilyl compound means a compound represented by Si(OH)4. In one embodiment, the trihydroxysilyl compound is represented by the following general formula: RSi(OH)3 (wherein R represents a substituted or unsubstituted alkyl group, vinyl group, or (meth)acryloxy group, and the substituents are exemplified by amino group, mercapto group, glycidoxy group, (meth)acryloxy group, epoxy group, etc.). The hydroxysilyl compound is preferably prepared by hydrolyzing a silane coupling agent or tetraalkoxysilane. The hydroxysilyl compound may be partially polycondensed within a range that does not lose water solubility. The silane coupling agent may be a commonly used silane coupling agent. The silane coupling agent is not particularly limited. The hydroxysilyl compound produced from the silane coupling agent may be used alone or in combination of two or more kinds. In one embodiment, the hydroxysilyl compound includes trihydroxysilylpropylamine. Examples of trialkoxysilanes include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, tetrahydroxysilane, etc. Examples of tetraalkoxysilanes include tetramethoxysilane, tetramethoxysilane oligomer, tetraethoxysilane, tetraethoxysilane oligomer, etc. Of these, from the viewpoints of stability and electrolyte resistance, it is preferable to use 3-aminopropyltrimethoxysilane to produce a hydroxysilyl compound.

[0124] Examples of additives other than those mentioned above include at least one compound selected from the group consisting of unsaturated carboxylic acids, unsaturated amides, and salts thereof.

[0125] The above-mentioned thermally crosslinkable binder aqueous solution for a lithium ion battery can be used as a thermally crosslinkable binder aqueous solution for a lithium ion battery negative electrode.

[0126] [Thermal crosslinking slurry for lithium-ion battery anodes: also called slurry] The present disclosure provides a thermally crosslinkable slurry for a lithium ion battery negative electrode, comprising the above-mentioned aqueous thermally crosslinkable binder solution for a lithium ion battery and a negative electrode active material.

[0127] In this disclosure, "slurry" means a suspension of liquid and solid particles.

[0128] Examples of the upper and lower limits of the pH of the thermally crosslinkable slurry for a lithium ion battery negative electrode include 7, 6.9, 6.5, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, and 5. In one embodiment, the pH of the thermally crosslinkable slurry for a lithium ion battery negative electrode is preferably 5 to 7 from the viewpoint of solution stability, and more preferably 5 or more and less than 7. From the viewpoint of preventing a decrease in slurry dispersibility and Coulombic efficiency, the pH is preferably 5 or more, and from the viewpoint of preventing a decrease in flexibility, the pH is preferably 7 or less.

[0129] <Negative electrode active material> The negative electrode active materials may be used alone or in combination of two or more kinds.

[0130] The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium, and an appropriate material can be selected depending on the type of the target lithium ion battery. Examples of the negative electrode active material include carbon materials, silicon materials, oxides containing lithium atoms, lead compounds, tin compounds, arsenic compounds, antimony compounds, and aluminum compounds that are alloyed with lithium.

[0131] Carbon materials and materials that form an alloy with lithium have a large volume expansion rate when the battery is charged, and therefore the effects of the present invention can be significantly exhibited.

[0132] The above carbon materials include graphite, which is highly crystalline carbon (also called black lead, and examples include natural graphite, artificial graphite, etc.), low-crystalline carbon (soft carbon, hard carbon), carbon black (Ketjen black, acetylene black, channel black, lamp black, oil furnace black, thermal black, etc.), fullerene, carbon nanotube, carbon nanofiber, carbon nanohorn, carbon fibril, mesocarbon microbeads (MCMB), pitch-based carbon fiber, etc.

[0133] In addition to silicon, silicon oxide, and silicon alloy, the above silicon materials include SiC, SiO x C y (0 < x ≤ 3, 0 < y ≤ 5), Si3N4, Si2N2O, SiO x Silicon oxide composites represented by (0 < x ≤ 2) (such as the materials described in JP-A-2004-185810 and JP-A-2005-259697), silicon materials described in JP-A-2004-185810, etc. are exemplified. Further, the silicon materials described in Patent No. 5390336 and Patent No. 5903761 may also be used.

[0134] The above silicon oxide has a composition formula SiO x Silicon oxide represented by (0 < x < 2, preferably 0.1 ≤ x ≤ 1) is preferred.

[0135] The above silicon alloy is preferably an alloy of silicon and at least one transition metal selected from the group consisting of titanium, zirconium, nickel, copper, iron, and molybdenum. These transition metal silicon alloys are preferred because they have high electron conductivity and high strength. The silicon alloy is more preferably a silicon-nickel alloy or a silicon-titanium alloy, and particularly preferably a silicon-titanium alloy. The content ratio of silicon in the silicon alloy is preferably 10 mol% or more, more preferably 20 to 70 mol%, based on 100 mol% of the metal elements in the above silicon alloy. Note that the silicon material may be any of single crystal, polycrystal, and amorphous.

[0136] In addition, when using a silicon material as the negative electrode active material, a negative electrode active material other than the silicon material may be used in combination. Such negative electrode active materials include the above carbon materials; conductive polymers such as polyacene; A X B Y O Z (A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, manganese, etc., O represents an oxygen atom, and X, Y, and Z are numbers in the ranges of 0.05 < X < 1.10, 0.85 < Y < 4.00, and 1.5 < Z < 5.00, respectively.) Composite metal oxides represented by, and other metal oxides, etc. are exemplified. When using a silicon material as the negative electrode active material, since the volume change accompanying the occlusion and release of lithium is small, it is preferable to use a carbon material in combination.

[0137] The above oxides containing lithium atoms are ternary lithium nickel cobalt manganese oxide, lithium-manganese composite oxide (such as LiMn2O4), lithium-nickel composite oxide (such as LiNiO2), lithium-cobalt composite oxide (such as LiCoO2), lithium-iron composite oxide (such as LiFeO2), lithium-nickel-manganese composite oxide (LiNi 0.5 Mn 0.5 O2, etc.), lithium-nickel-cobalt composite oxide (LiNi 0.8 Co 0.2 O2, etc.), lithium-transition metal phosphate compounds (such as LiFePO4), and lithium-transition metal sulfate compounds (Li x Fe2(SO4)3), lithium-titanium composite oxide (lithium titanate: Li4Ti5O 12 ), etc. lithium-transition metal composite oxides, and other conventionally known negative electrode active materials, etc. are exemplified.

[0138] The shape of the negative electrode active material is not particularly limited, and may be any shape such as fine particles or thin film, but is preferably fine particles. The average particle size of the negative electrode active material is not particularly limited, but the upper and lower limits are 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, 4, 3, 2.9, 2, 1, 0.5, 0.1 μm, etc. In one embodiment, the average particle size of the negative electrode active material is preferably 0.1 to 50 μm, more preferably 0.1 to 45 μm, even more preferably 1 to 10 μm, and particularly preferably about 5 μm. If it is 0.1 μm or more, the handling property is good, and if it is 50 μm or less, the application of the electrode is easy. If it is in such a range, it is preferable because a uniform and thin coating film can be formed.

[0139] In this disclosure, the term "particle size" refers to the maximum distance between any two points on the contour of a particle (hereinafter the same). In addition, in this disclosure, the term "average particle size" refers to a value calculated as the average particle size of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM) unless otherwise specified (hereinafter the same).

[0140] In order to prominently exhibit the effects of the present invention, the negative electrode active material contains a carbon material and / or a material that can be alloyed with lithium in an amount of preferably 50 mass % or more, more preferably 80 mass % or more, even more preferably 90 mass % or more, and particularly preferably 100 mass %.

[0141] In one embodiment, the content of silicon or silicon oxide covered with a carbon layer in the negative electrode active material is preferably 5% by mass or more (e.g., 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 100% by mass) relative to 100% by mass of the negative electrode active material, from the viewpoint of increasing the battery capacity of a lithium ion battery.

[0142] The upper and lower limits of the content of the component (A) relative to 100% by mass of the above slurry are, for example, 15, 14, 12, 10, 9, 7, 5, 4, 3, 2, 1, 0.9, 0.6, 0.5% by mass, etc. In one embodiment, the content is preferably 0.5 to 15% by mass.

[0143] The upper and lower limits of the content of the component (A) relative to 100% by mass of the negative electrode active material in the slurry are, for example, about 15, 14, 11, 10, 9, 5, 4, 2 and 1% by mass. In one embodiment, the content is preferably about 1 to 15% by mass.

[0144] The upper and lower limits of the content of the negative electrode active material relative to 100% by mass of the slurry are, for example, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20% by mass, etc. In one embodiment, the content relative to 100% by mass of the slurry is preferably 20 to 65% by mass.

[0145] The upper and lower limits of the water content relative to 100% by mass of the slurry are, for example, 79, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20% by mass, etc. In one embodiment, the content is preferably 20 to 79% by mass.

[0146] The slurry may contain a binder other than the water-soluble poly(meth)acrylamide (A). In one embodiment, the water-soluble poly(meth)acrylamide (A) is preferably present in an amount of 90% by mass or more (e.g., 95, 99% by mass or more, 100% by mass, etc.) in the total binder.

[0147] <Slurry viscosity adjusting solvent> The slurry viscosity adjusting solvent is not particularly limited, and may include a non-aqueous medium having a normal boiling point of 80 to 350° C. The slurry viscosity adjusting solvent may be used alone or in combination of two or more kinds. Examples of the slurry viscosity adjusting solvent include amide solvents such as N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide; hydrocarbon solvents such as toluene, xylene, n-dodecane, and tetralin; alcohol solvents such as methanol, ethanol, 2-propanol, isopropyl alcohol, 2-ethyl-1-hexanol, 1-nonanol, and lauryl alcohol; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, phorone, acetophenone, and isophorone; ether solvents such as dioxane and tetrahydrofuran (THF); ester solvents such as benzyl acetate, isopentyl butyrate, methyl lactate, ethyl lactate, and butyl lactate; amine solvents such as o-toluidine, m-toluidine, and p-toluidine; lactones such as γ-butyrolactone and δ-butyrolactone; sulfoxide and sulfone solvents such as dimethyl sulfoxide and sulfolane; and water. Among these, N-methylpyrrolidone is preferred from the viewpoint of coating workability. The content of the non-aqueous medium is not particularly limited, but is preferably 0 to 10% by mass relative to 100% by mass of the slurry.

[0148] Attempts have been made to thermally crosslink the binder resin in the electrode by adding a crosslinking agent to the binder or slurry, coating the slurry on a current collector, and drying it (for example, materials described in International Publication No. 2015 / 098507). This crosslinks the binder resin in the electrode, which has the effect of suppressing the expansion of the active material layer associated with charge / discharge cycles. The above thermally crosslinkable binder aqueous solution also has the effect of suppressing the expansion of the active material layer associated with charge / discharge cycles by thermally crosslinking the binder resin in the electrode. The above thermally crosslinkable binder aqueous solution, or the thermally crosslinkable slurry using the thermally crosslinkable binder aqueous solution, has excellent storage stability. The storage stability can be evaluated by measuring the solution viscosity of the prepared thermally crosslinkable binder aqueous solution or thermally crosslinkable slurry with a B-type viscometer, storing it in an oven heated to 40 ° C. for 3 days, and measuring the solution viscosity after storage with a B-type viscometer again to check for any change in viscosity.

[0149] <Additives> The above-mentioned slurry may contain an additive that does not fall under any of the (A) component, the negative electrode active material, water, and the slurry viscosity adjusting solvent. The content of the additive is, for example, 0 to 5 mass%, less than 1 mass%, less than 0.1 mass%, less than 0.01 mass%, 0 mass%, etc., relative to 100 mass% of the above-mentioned slurry. The additive is, for example, the above-mentioned additives.

[0150] The above slurry contains 2 to 60 mol % of a constituent unit derived from a (meth)acrylamide group-containing compound (a), and A water-soluble poly(meth)acrylamide (A) containing 10 to 50 mol % of structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b). and a step of producing an aqueous solution of a thermally crosslinkable binder for a lithium ion battery, the aqueous solution containing 0.5 to 30 mol % of divalent or higher metal ions relative to 100 mol % of the acid groups of the component (b); and A step of mixing the aqueous thermally crosslinkable binder solution for lithium ion batteries with a negative electrode active material. The composition can be produced by a production method including the steps of:

[0151] The method for producing the slurry includes, for example, a method of mixing the aqueous solution of the component (A) (the aqueous solution of the thermally crosslinkable binder for lithium ion batteries) with the negative electrode active material, and a method of separately mixing the component (A), the negative electrode active material, and water. The order of mixing in the above method is not particularly limited. Examples of the means for mixing the slurry include a ball mill, a sand mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, a Hobart mixer, and the like.

[0152] [Lithium-ion battery negative electrode] The present disclosure provides a lithium ion battery negative electrode obtained by applying the thermally crosslinkable slurry for lithium ion battery negative electrodes to a current collector, followed by drying and curing the slurry. The electrode has a cured product of the thermally crosslinkable slurry for lithium ion battery negative electrodes on a current collector.

[0153] The current collector may be any of various known current collectors without any particular limitation. The material of the current collector is not particularly limited, and examples thereof include metal materials such as copper, iron, aluminum, nickel, stainless steel, and nickel-plated steel, and carbon materials such as carbon cloth and carbon paper. The form of the current collector is also not particularly limited, and examples of metal materials include metal foil, metal cylinder, metal coil, and metal plate, and examples of carbon materials include carbon plate, carbon thin film, and carbon cylinder. Among them, when the electrode active material is used for the negative electrode, copper foil is preferred as the current collector because it is currently used in industrialized products.

[0154] The coating means is not particularly limited, and examples thereof include conventionally known coating devices such as a comma coater, a gravure coater, a microgravure coater, a die coater, and a bar coater.

[0155] The drying method is not particularly limited, and the temperature is preferably about 80 to 200° C., more preferably about 90 to 180° C., and the atmosphere may be dry air or an inert atmosphere. Drying at an appropriate temperature advances crosslinking of the water-soluble poly(meth)acrylamide (A), which is a thermally crosslinkable binder for lithium ion batteries, and exhibits springback resistance associated with charge / discharge cycles.

[0156] The thickness of the negative electrode (cured product) is not particularly limited, but is preferably 5 to 300 μm, and more preferably 10 to 250 μm. By setting the thickness within the above range, it may become easier to obtain a sufficient Li absorption / release function for a high-density current value.

[0157] [Lithium-ion battery] The present disclosure provides a lithium ion battery including the above-mentioned negative electrode for lithium ion batteries. In one embodiment, the battery includes an electrolyte solution, a separator, a positive electrode, and the like. These are not particularly limited.

[0158] The electrolyte solution may be, for example, a non-aqueous electrolyte solution in which a supporting electrolyte is dissolved in a non-aqueous solvent, etc. The non-aqueous electrolyte solution may also contain a film-forming agent.

[0159] As the non-aqueous solvent, various known solvents can be used without any particular limitation, and may be used alone or in combination of two or more. Examples of the non-aqueous solvent include chain carbonate solvents such as diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate; cyclic carbonate solvents such as ethylene carbonate, propylene carbonate, and butylene carbonate; chain ether solvents such as 1,2-dimethoxyethane; cyclic ether solvents such as tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane; chain ester solvents such as methyl formate, methyl acetate, and methyl propionate; cyclic ester solvents such as γ-butyrolactone and γ-valerolactone; and acetonitrile. Among these, a combination of a mixed solvent containing a cyclic carbonate and a chain carbonate is preferred.

[0160] The supporting electrolyte is a lithium salt. Various known lithium salts can be used without particular limitation, and may be used alone or in combination of two or more. Examples of the supporting electrolyte include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among them, LiPF6, LiClO4, and CF3SO3Li, which are easily soluble in a solvent and show a high degree of dissociation, are preferred. The higher the degree of dissociation of the supporting electrolyte used, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0161] The coating agent may be any of various known agents without particular limitation, and may be used alone or in combination of two or more. Examples of the coating agent include carbonate compounds such as vinylene carbonate, vinyl ethylene carbonate, vinyl ethyl carbonate, methyl phenyl carbonate, fluoroethylene carbonate, and difluoroethylene carbonate; alkene sulfides such as ethylene sulfide and propylene sulfide; sultone compounds such as 1,3-propane sultone and 1,4-butane sultone; and acid anhydrides such as maleic anhydride and succinic anhydride. The content of the coating agent in the electrolyte solution is not particularly limited, but is preferably 10% by mass or less, 8% by mass or less, 5% by mass or less, and 2% by mass or less in that order. By setting the content to 10% by mass or less, it becomes easier to obtain the advantages of the coating agent, such as suppression of initial irreversible capacity and improvement of low-temperature characteristics and rate characteristics.

[0162] The separator is an article interposed between the positive electrode and the negative electrode, and is used to prevent short circuit between the electrodes. Specifically, a porous separator such as a porous membrane or a nonwoven fabric can be preferably used, and is used by impregnating the nonaqueous electrolyte solution. The separator is made of a polyolefin such as polyethylene or polypropylene, or polyethersulfone, and is preferably made of polyolefin.

[0163] The positive electrode may be any of various known positive electrodes without any particular limitations. Examples of the positive electrode include a positive electrode obtained by mixing a positive electrode active material, a conductive assistant, and a positive electrode binder with an organic solvent to prepare a slurry, and applying the prepared slurry to a positive electrode current collector, drying, and pressing the slurry.

[0164] The positive electrode active material is exemplified by inorganic positive electrode active material and organic positive electrode active material. The inorganic positive electrode active material is exemplified by transition metal oxide, composite oxide of lithium and transition metal, transition metal sulfide, etc. The transition metal is exemplified by Fe, Co, Ni, Mn, Al, etc. Inorganic compounds used for the positive electrode active material are LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, LiNi 1 / 2 Mn 3 / 2 O4, LiCo1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li [Li 0.1 Al 0.1 Mn 1.8 ]O4, LiFeVO4 and other lithium-containing composite metal oxides; TiS2, TiS3, amorphous MoS2 and other transition metal sulfides; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, V6O 13 Examples of the organic positive electrode active material include conductive polymers such as polyacetylene and poly-p-phenylene. Iron-based oxides, which have poor electrical conductivity, may be used as an electrode active material covered with a carbon material by making a carbon source material present during reduction and firing. Also, these compounds may be partially substituted with elements. Among these, in terms of practicality, electrical properties, and long life, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, LiNi 1 / 2 Mn 3 / 2 O4, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li [Li 0.1 Al 0.1 Mn 1.8 ]O4 is preferred.

[0165] Examples of the conductive assistant include fibrous carbon such as vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and carbon nanofiber (CNF), graphite particles, carbon black such as acetylene black, ketjen black, and furnace black, and fine powders of Cu, Ni, Al, Si, or alloys thereof having an average particle size of 10 μm or less.

[0166] The positive electrode binder may be any of various known binders without particular limitation, and may be used alone or in combination of two or more. Examples of the positive electrode binder include fluorine-based resins (polyvinylidene fluoride, polytetrafluoroethylene, etc.), polyolefins (polyethylene, polypropylene, etc.), polymers having unsaturated bonds (styrene-butadiene rubber, isoprene rubber, butadiene rubber, etc.), and acrylic acid-based polymers (acrylic acid copolymers, methacrylic acid copolymers, etc.).

[0167] The positive electrode current collector is exemplified by an aluminum foil, a stainless steel foil, and the like.

[0168] The shape of the lithium ion battery is not particularly limited. Examples of the shape of the lithium ion battery include a cylinder type in which a sheet electrode and a separator are spirally wound, a cylinder type with an inside-out structure in which a pellet electrode and a separator are combined, and a coin type in which a pellet electrode and a separator are laminated. In addition, by housing a battery of these shapes in an arbitrary exterior case, it can be used in an arbitrary shape such as a coin type, a cylindrical type, or a square type.

[0169] The method for manufacturing the lithium ion battery is not particularly limited, and the battery may be assembled in an appropriate procedure according to the structure of the battery. The lithium ion battery may be manufactured, for example, by the method described in JP 2013-089437 A. The battery can be manufactured by placing a negative electrode on an exterior case, providing an electrolyte and a separator thereon, placing a positive electrode facing the negative electrode, and fixing them with a gasket and a sealing plate. EXAMPLES

[0170] The present invention will be specifically described below through examples and comparative examples. However, the above-mentioned description of the preferred embodiment and the following examples are provided for illustrative purposes only and are not provided for the purpose of limiting the present invention. Therefore, the scope of the present invention is not limited to the embodiments or examples specifically described in this specification, but is limited only by the claims. In each example and comparative example, unless otherwise specified, numerical values ​​such as parts and % are based on mass.

[0171] 1. (A) Production of component Example 1-1 In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, 1200g of ion-exchanged water, 100g (0.70mol) of 50% acrylamide aqueous solution, 63.6g (0.70mol) of 80% acrylic acid, 70.1g (0.60mol) of 2-hydroxyethyl acrylate, and 0.32g (0.0020mol) of sodium methallylsulfonate were placed, and oxygen in the reaction system was removed by passing nitrogen gas through it, after which the temperature was raised to 55°C. 1.7g of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Nippoh Chemical Co., Ltd., product name "NC-32") and 15g of ion-exchanged water were placed therein, and the temperature was raised to 80°C and the reaction was carried out for 3 hours. Then, 52.9 g (0.63 mol) of 48% sodium hydroxide solution and 0.26 g (0.0035 mol) of calcium hydroxide were added as neutralizing agents and stirred, and ion-exchanged water was added so that the solid content concentration became 13%, to obtain an aqueous solution containing water-soluble polyacrylamide. The pH of this solution at 25°C was 6.0.

[0172] In Example 1 other than Example 1-1, an aqueous solution containing a water-soluble poly(meth)acrylamide was prepared in the same manner as in Example 1-1, except that the monomer composition and the amount of neutralizing agent in Example 1-1 were changed to those shown in Table 1.

[0173] Comparative Example 1-1 In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, 1200g of ion-exchanged water, 100g (0.70mol) of 50% acrylamide aqueous solution, 63.6g (0.70mol) of 80% acrylic acid, 70.1g (0.60mol) of 2-hydroxyethyl acrylate, and 0.32g (0.0020mol) of sodium methallylsulfonate were placed, and oxygen in the reaction system was removed by passing nitrogen gas through it, and the temperature was raised to 55°C. 1.7g of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Nippoh Chemical Co., Ltd., product name "NC-32") and 15g of ion-exchanged water were placed therein, and the temperature was raised to 80°C and the reaction was carried out for 3 hours. Then, 52.9g (0.63mol) of 48% sodium hydroxide aqueous solution was added as a neutralizing agent and stirred, and ion-exchanged water was added so that the solid concentration was 13%, to obtain an aqueous solution containing water-soluble polyacrylamide. The pH of this solution at 25° C. was 6.0.

[0174] In Comparative Example 1 other than the above Comparative Example 1-1, an aqueous solution containing a water-soluble poly(meth)acrylamide was prepared in the same manner as in Comparative Example 1-1, except that the monomer composition and the amount of neutralizing agent in Comparative Example 1-1 were changed to those shown in Table 1.

[0175] B type viscosity The viscosity of each aqueous binder solution was measured at 25° C. under the following conditions using a Brookfield viscometer (manufactured by Toki Sangyo Co., Ltd., product name: Brookfield viscometer model BM). Uses No.3 rotor, rotation speed 12 rpm.

[0176] Weight average molecular weight The weight average molecular weight was determined as a polyacrylic acid equivalent value measured by gel permeation chromatography (GPC) in a 0.2 M phosphate buffer / acetonitrile solution (90 / 10, pH 8.0). The GPC apparatus used was HLC-8220 (manufactured by Tosoh Corporation), and the column used was SB-806M-HQ (manufactured by SHODEX).

[0177] pH The pH of each binder aqueous solution was measured at 25° C. using a glass electrode pH meter (product name: "Handy pH Meter D-52", manufactured by Horiba, Ltd.).

[0178] Gel fraction 10 g of a thermally crosslinkable binder solution for lithium ion batteries containing water-soluble poly(meth)acrylamide (A) was placed in an ointment can (manufactured by Sogo Rikagaku Glass Works, product name "Ointment Can Tinplate") and dried at 120°C for 4 hours in a circulating air dryer (manufactured by Advantec Toyo Co., Ltd., product name "Air-Blowing Constant Temperature Dryer DSR420DA") to obtain a solid resin after thermal crosslinking. The mass of the solid resin was accurately measured at 25°C using a mass meter (manufactured by Sartorius Japan, product name "Standard Balance CPA324S"). The measured solid resin was transferred to a container (300 mL beaker) containing 150 mL of pure water, and immersed in water at 25 ° C for 3 hours under stirring conditions using a magnetic stirrer (manufactured by Tokyo Rikakikai Co., Ltd., product name "Strong Magnetic Stirrer RCX-1000D"), and then filtered under reduced pressure with filter paper (manufactured by Kiriyama Seisakusho Co., Ltd., "No. 50B") using a Kiriyama funnel (manufactured by Kiriyama Seisakusho Co., Ltd., product name "Kiriyama Funnel SB-60") and a suction bell (manufactured by Kiriyama Seisakusho Co., Ltd., product name "Suction Bell VKB-200") The insoluble residue remaining on the filter paper was then dried at 120 ° C for 3 hours in the above-mentioned air circulation dryer, and the mass of the insoluble residue was accurately measured with the above-mentioned mass meter at 25 ° C., and the gel fraction of the resin after thermal crosslinking of the water-soluble battery binder was calculated from the following formula. Gel fraction (%) = {insoluble residue (g) / mass of solid resin (g)} x 100

[0179] [Table 1] AM: Acrylamide (Mitsubishi Chemical Corporation "50% Acrylamide") ·DMAA: N,N-Dimethylacrylamide ("DMAA" manufactured by KJ Chemicals Co., Ltd.) AA: Acrylic acid (Osaka Organic Chemical Industry Co., Ltd. "80% acrylic acid") ATBS: Acrylamide t-butyl sulfonic acid (manufactured by Toagosei Co., Ltd. "ATBS") ·HEA: 2-hydroxyethyl acrylate ("HEA" manufactured by Osaka Organic Chemical Industry Ltd.) HBA: 4-hydroxybutyl acrylate (Mitsubishi Chemical Corporation "4HBA") AN: Acrylonitrile (Mitsubishi Chemical Corporation "Acrylonitrile") ·SMAS: Sodium methallyl sulfonate NaOH: Sodium hydroxide (Kanto Chemical Co., Ltd. "48% sodium hydroxide solution") LiOH: Lithium hydroxide ("Lithium hydroxide monohydrate" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Ca(OH)2: Calcium hydroxide ("Calcium hydroxide" manufactured by Kishida Chemical Co., Ltd.)

[0180] 2. Slurry production, cell construction and evaluation Example 2-1 Using a commercially available planetary centrifugal mixer (product name "Awatori Rentaro", manufactured by Thinky Corporation), 5 parts by mass of a thermally crosslinkable binder aqueous solution for lithium ion batteries containing the water-soluble poly(meth)acrylamide (A) obtained in Example 1-1, 20 parts by mass of silicon monoxide particles ("CC Powder", manufactured by Osaka Titanium Technologies Co., Ltd.) having a D50 (median diameter) of 5 μm, and 80 parts by mass of natural graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "Z-5F") were mixed in a container dedicated to the mixer. Ion-exchanged water was added thereto so that the solid concentration was 40%, and the container was set in the mixer. Next, the mixture was kneaded at 2000 rpm for 10 minutes, and then defoamed for 1 minute to obtain a slurry.

[0181] In Example 2 and Comparative Examples other than Example 2-1, slurries were prepared in the same manner as in Example 2-1, except that the composition in Example 2-1 was changed to that shown in Table 2.

[0182] <Storage stability test of electrode slurry> The viscosity of the electrode slurry (unit: mPa s) was measured using a Brookfield viscometer, and then it was stored in an oven heated to 40°C for three days. After storage, the viscosity was measured again using the Brookfield viscometer, and the change in viscosity was calculated using the following formula and evaluated according to the following criteria. Viscosity change (%) = (viscosity of electrode slurry after storage) / (viscosity of electrode slurry before storage) × 100 A: Less than 110% B: 110% or more but less than 120% C: 120% or more but less than 130% D: 130% or more

[0183] <Electrode manufacturing> The above-mentioned slurry for lithium ion batteries was uniformly applied to the surface of a current collector made of copper foil by a doctor blade method so that the film thickness after drying would be 170 μm, and after drying at 150 °C for 30 minutes, it was heat-treated at 150 °C / vacuum for 120 minutes to obtain an electrode. After that, the density of the film (electrode active material layer) was 1.5 g / cm 3 The electrode was obtained by pressing the electrode sheet with a roll press machine so that the electrode sheet had a thickness of 100 mm.

[0184] <Electrode Adhesion Evaluation> The electrode adhesion was evaluated as follows. A test piece measuring 2 cm wide x 10 cm long was cut out from the electrode and fixed with the coating surface facing up. Next, a 15 mm wide adhesive tape ("Cellotape (registered trademark)" manufactured by Nichiban Co., Ltd.) (specified in JIS Z1522) was applied to the surface of the active material layer of the test piece while pressing it, and then the stress was measured when the adhesive tape was peeled off from one end of the test piece in the 180° direction at a speed of 30 mm / min using a tensile tester ("Tensilon RTM-100" manufactured by A&D Co., Ltd.) under conditions of 25°C. The measurement was performed twice, converted into a value per 15 mm width, and the average value was calculated as the peel strength. The higher the peel strength, the higher the adhesion strength between the current collector and the active material layer or the binding strength between the active materials, indicating that the active material layer or the active materials are less likely to peel off from the current collector.

[0185] <Assembling lithium half-cells> In an argon-substituted glove box, the above electrode was punched out to a diameter of 16 mm and placed inside the packing on the Al bottom cover of a test cell (manufactured by Nippon Tomcell Co., Ltd.). Next, a separator made of a polypropylene porous film punched out to a diameter of 24 mm (manufactured by CS TECH CO., LTD, product name "Selion P2010") was placed, and 500 μL of electrolyte was poured in to prevent air from entering, and then a commercially available metallic lithium foil punched out to a diameter of 16 mm was placed on the separator. The exterior body of the test cell was closed and sealed with screws to assemble a lithium half cell. The electrolyte used here was a solution in which LiPF6 was dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).

[0186] <Charge / discharge measurement> The lithium half-cell was placed in a thermostatic chamber at 25° C., and charging was started at a constant current (0.1 C), and charging was completed (cut off) when the voltage reached 0.01 V. Next, discharging was started at a constant current (0.1 C), and charging and discharging was repeated 30 times, with discharging completed (cut off) when the voltage reached 1.0 V. In the above measurement conditions, "1C" refers to the current value at which a cell with a certain capacity is discharged at a constant current and the discharge is completed in 1 hour. For example, "0.1C" refers to the current value at which the discharge is completed in 10 hours, and "10C" refers to the current value at which the discharge is completed in 0.1 hour.

[0187] <Discharge capacity maintenance rate> The discharge capacity retention rate was calculated according to the following formula. Discharge capacity retention rate = {(discharge capacity at 30th cycle) / (discharge capacity at 1st cycle)} x 100 (%)

[0188] <Springback rate measurement> After 30 charge-discharge cycle tests at room temperature (25°C), the lithium half-cell was disassembled and the thickness of the electrodes was measured. The springback rate of the electrodes was calculated using the following formula. Springback rate = {(electrode thickness after 30 cycles - current collector thickness) / (electrode thickness before charge / discharge - current collector thickness)} x 100 - 100 (%)

[0189] [Table 2]

[0190] As is clear from Table 2, the slurries prepared using the aqueous binder solutions of the examples and the lithium half-cells prepared from these slurries were evaluated to be good in terms of storage stability, electrode adhesion, discharge capacity retention rate, and springback rate.

Claims

1. 2 to 60 mol % of a structural unit derived from a (meth)acrylamide group-containing compound (a), and A water-soluble poly(meth)acrylamide (A) containing 20 to 50 mol % of structural units derived from one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids or inorganic salts thereof (b). and an aqueous thermally crosslinkable binder solution for lithium ion batteries, comprising 0.5 to 30 mol % of divalent or higher metal ions relative to 100 mol % of the acid groups of the component (b).

2. 2. The thermally crosslinkable binder aqueous solution for lithium ion batteries according to claim 1, wherein the water-soluble poly(meth)acrylamide (A) contains 15 to 75 mol % of a structural unit derived from the hydroxyl group-containing (meth)acrylic ester (c).

3. 3. The thermally crosslinkable binder aqueous solution for lithium ion batteries according to claim 1, wherein the divalent or higher metal ion is a calcium ion.

4. A thermally crosslinkable slurry for a lithium ion battery negative electrode, comprising the thermally crosslinkable binder aqueous solution for a lithium ion battery according to any one of claims 1 to 3 and a negative electrode active material.

5. A negative electrode for a lithium ion battery having a cured product of the thermally crosslinkable slurry for a lithium ion battery negative electrode described in claim 4 on a current collector.

6. A lithium ion battery comprising the negative electrode for a lithium ion battery according to claim 5.

Citation Information

Patent Citations

  • Slurry for electricity storage device negative electrode and electricity storage device negative electrode, slurry for electricity storage device positive electrode and electricity storage device positive electrode, and electricity storage device

    JP2015106488A

  • Binder composition for electricity storage device, slurry for electricity storage device, electricity storage device electrode, separator, and electricity storage device

    JP2015118908A

  • Binder aqueous solution for lithium ion battery, slurry for lithium ion battery, manufacturing methods thereof, electrode for lithium ion battery, separator for lithium ion battery, separator / electrode laminate for lithium ion battery and lithium ion battery

    JP2019057486A

  • Slurry for thermal crosslinking type lithium ion battery, manufacturing method thereof, electrode for lithium ion battery, separator for lithium ion battery, separator / electrode laminate for lithium ion battery, and lithium ion battery

    JP2019057488A

  • Binder composition for lithium ion secondary battery, slurry composition for lithium ion secondary battery, method for manufacturing electrode for secondary battery, and lithium ion secondary battery

    WO2015098507A1